UV light and temperature induced fluridone degradation in water and sediment and potential transport into aquifer. (October 2020) - Wickham, Patrick; Pandey, Pramod; Harter, Thomas; Sandovol-Solis, Samuel
Abstract: Fluridone is widely used in ambient water bodies to control the spread of invasive aquatic plants. While the ability of fluridone to control aquatic weeds such as water hyacinth is well reported, an improved understanding of fluridone persistence in water and sediment is still needed to determine potential residues of fluridone in the water column and bed sediment of ambient water bodies. In this study, experiments were conducted over a three-month period to examine the degradation of fluridone in saturated sediment and water under various levels of UV-light (0–1000 μW/cm 2 ), and temperature (4–40 °C). Results showed a large decrease in the half-life of fluridone in water with increasing UV light intensity, but in saturated sediment the impact of UV light exposure on fluridone degradation was minimal. At low temperature (4 °C), the degradation of fluridone in both water and sediment was minimal. At elevated temperature (20–40 °C), fluridone degradation was increased in water and sediment. Additionally, the persistence of fluridone in sediment was reduced by increasing sand content in the sediment matrix. Possible fluridone transport through the subsurface was estimated over a range of initial concentrations, groundwater velocities, fluridone half-lives, and fluridone sorption coefficients which may be seen in a field environment. A form of the Ogata-Banks equation which accounts for 1st order decay was used for describing the dispersion of fluridone, while a related equation from Bear, 1979 was utilized to quantify advection. In all tested scenarios, maximum transport was less than 10 m over one month of observation. Results of this study will improve our existing understanding of fluridone persistence and in water and sediment. Graphical abstract: Image 1 Highlights: Photodegradation of fluridone in water increases with increasing UV light. At low temperature fluridone persisted for more than 70 days. Elevated temperature resulted in reduced fluridone concentrations in water and sediment. Fluridone persistence is prolonged by increasing clay content. Fluridone subsurface transport is limited to less than 10 m over 1 month. Abstract : This work quantifies the effect of environmental factors on the half-life of the herbicide fluridone in water and sediment and estimates possible fluridone transport through the subsurface, helping to inform sustainable herbicide application in aquatic environments.